Penanaman Nilai-Nilai Karakter Sosial Siswa Dalam Pendidikan Kewarganegaraan Dan Ips Dalam Konteks Perpspektif Global - Tetep (Pendidikan Teknologi Informasi, 2016)
Abstract – The 21st century is a major challenge for the development of general education in preparing young people in the nation and the wider life without limits. Education became the center of the adjustment of each individual role as the public face of the world today. Global perspective becomes an important education is taught by any educational institution in order to give birth to a generation that is able to compete in the global life without losing its local characteristics. Social character student that grows naturally in the local life will become a symbol of strength and intelligence implementation of local values developed in the global life through education system. Civic and social studies education as subject which cannot be relased to the developing and changes of society. Civic and social studies educatioan has a major role in bridging of social character education for the student to be humanize. Keywords – global perspective education, social character, humanize.